Pendampingan Pengembangan Usaha UMKM Bakso Pada Masa Pandemi - I Made Sandi Pria Winarta; Ni Kadek Ratna Dewi; Komang Budi Artawan Putra; Luh Putu Mahyuni (Universitas Lancang Kuning, 2022)
During a pandemic, MSMEs actors must be more innovative and creative in packaging and marketing their products in order to be able to survive and develop. In this service, the writer uses the method of observation and interviews with partners, namely MSMEs, Pak Robin, and then finds the problems faced by Mr. Robin, namely the packaging of products that are less creative and innovative and marketing of products that are still conventional. interesting and innovative and will share and educate how to market through Instagram social media. The purpose of this activity is to help and educate Mr. Robin's UMKM so that they can survive and thrive during the pandemic.